Editorial: Neurobiological and psychophysiological underpinnings of wellbeing and prosocial connectedness - Darren Edwards (Frontiers in Integrative Neuroscience, 2022)
The autonomic nervous system (ANS) and associated neurobiological pathways connecting the brain and body play a central role in health and wellbeing. For example, deficient vagal-nerve-related functioning such as interoception (sensory signals originating from inside the body which are carried by the vagal nerve to the brain) and low heart rate variability (HRV) have been linked to a range of mental health conditions, including mood and anxiety disorders, developmental, and eating disorders (Paulus and Stein, 2010; Chalmers et al., 2014; Jenkinson et al., 2018; Khalsa et al., 2018). Furthermore, a key driver of mental and physical wellbeing is the capacity for social connection; an ability that starts to develop during early childhood (Skinner and Zimmer-Gembeck, 2016). However, there is a lack of normative data concerning aspects of vagal-related functioning at different developmental stages. Finally, there is a paucity of evidence relating interoception and other forms of vagal functioning with developmental disorders such as autism spectrum disorders (ASD), or alexithymia.Given the lack of evidence in the mentioned areas, this Research Topic aimed to: (1) Identify the ways in which interoception and other forms of vagal functioning (e.g., HRV) relate to social connectedness, perspective-taking, and prosocial behavior; (2) Increase understanding of the mechanisms and developmental stages of vagal functioning in relation to prosocial behavior and social connection; (3) Identify how deficits in interoception and other forms of vagal functioning relates to deficits in communication such as in autism spectrum disorders (ASD) and alexithymia; and (4) Place emphasis on the role that interoception and other forms of vagal functioning play as mediating and moderating factors of wellbeing such as psychological flexibility.